EFFECTIVENESS OF CONCEPT ATTAINMENT MODEL (CAM) OF TEACHING ON THE ACHIEVEMENT OF SECONDARY SCHOOL STUDENTS IN BIOLOGICAL SCIENCE - Alam, Molla Jannatul Ferdousul Alam (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The present study intends to study the effectiveness of Concept Attainment Model of teaching on the achievement of class X students in biological science. A sample of 100 students of Secondary Schools was randomly selected for the study for each controlled and experimental group, out of sixty students 50 were male and 50 female students were selected as sample for the study. Descriptive and inferential statistics were used to compare the means between the groups and ‘t’ test was calculated to find the level of significance between the calculated means. The finding of the study revealed that the concept attainment model is useful in terms of achievement of students in the teaching of biological sciences. This study provides an additional insight into prior research conducted in concept attainment and its effect on learning. The findings reveal that concept attainment has a noticeable impact on students’ achievement in biological science so it should be promoted as a strategy of teaching science.